'It's just part of the disease': a qualitative study exploring help-seeking behaviours for fatigue in inflammatory bowel disease. (2nd June 2021) - Dhálaigh, Doireann Ní; Greaney, Anna Marie; Farrell, Dawn
Abstract : Background: Fatigue is the most burdensome aspect of inflammatory bowel disease (IBD). Despite this, people tend not to discuss fatigue or seek help. Aims: To uncover the reasons people do or do not seek help for fatigue in IBD. Methods: A qualitative approach was employed, underpinned by the Theory of Planned Behaviour. Semi-structured interview questions were posed to a voluntary sample of 12 participants with self-reported diagnosis of IBD fatigue, recruited from the Irish Society of Colitis and Crohn's. The sample included individuals who had and had not sought help in the past. Findings: The availability of management options, symptom perception, symptom impact, knowledge of sources of help and inferiority of fatigue as a symptom can influence help-seeking behaviour. Fatigue is viewed as inferior to other symptoms of IBD, which influences help-seeking behaviour and help-seeking experiences. Conclusions: Health professionals can increase help-seeking by informing patients about the symptom and identifying a specific source of help for fatigue.